Peran Sektor Pertanian dalam Perekonomian Negara Maju dan Negara Berkembang: Sebuah Kajian Literatur - Ibtihal Hidayah; Yulhendri Yulhendri; Nora Susanti (Jurnal Salingka Nagari, 2022)
This study aims to determine 1) the development of the agricultural sector in the economies of developed an developing countries, 2) the growth of agricultural sector in the economies of developed and developing countries, 3) the contribution of the agricultural sector to the economies of developed and developing countries, and 4) productivity of the agricultural sector in the economy of developed and developing countries. This study uses 50 analytical articles based on filtering articles based on the specified topic. The research method uses a systematic literature review. The data used is secondary data. The data sources used in the research were obtained from Lens.org and Google Scholar in the form of articles and journals. The results show that the development of the agricultural sector in the economy is a sector that a role in the country’s economy, both in developed and developing countries.